PENGARUH KOMITMEN ORGANISASI, PROFESIONALISME DAN RETALIASI TERHADAP INTENSI DALAM MELAKUKAN WHISTLEBLOWING PADA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN GIANYAR - Anak Agung Indah Puspita Dewi; I Putu Nuratama (UNHI Press, 2022)
Whistleblowing is disclosure of violations or reporting that occurs in an organization which is conducted by internal or external parties. This research to determine the effect of organizational commitment, professionalism and retaliation to the intention to do whistleblowing at the Lembaga Perkreditan Desa (LPD) in Gianyar sub-district. The population in this research were all employees of the LPD in Gianyar district. the sample in this research amounted to 223 respondents, but the data processed were 177 due to the outlier data as many as 46. The method of determining the sample using saturated sampling technique.This research was conducted by distributing questionnaires. The result of this research indicate that the organizational commitment has no significant effect on the intention to do whistleblowing, professionalism has no significant effect on the intention to do whistleblowing, and retaliation has a negative and significant effect on the intention to do whistleblowing.